Adapting a Design and Development Research (DDR) Approach in Designing the Mobile Application Model for Tarannum Subject - Hasbullah, Nurul Auji (Advances in Humanities and Contemporary Studies, 2023)
This study aims to develop a model of mobile application for Tarannum subject. The development of mobile application model was for KKQ (Kelas Khas Kemahiran Membaca dan Menghafaz al-Qur’an) Tarannum subject towards highlighting the meaning-based concept in the model developed. To achieve this goal, the design and development research (DDR) were applied in accordance with the procedure of three phases as systematic process in conducting the research which respectively are analysis phase, design and development phase, and evaluation phase. The design and development research approach is currently widely used in educational research to test theory and validate a study empirically. This approach is also known as developmental research or development research, which is used in this study to design and develop a model systematically in a practical way. According to the result of this study, the main components of meaning-based Tarannum mobile app model designed for KKQ class are Tarannum types, Tarannum variation (harakat), Qur’anic chapters in audio version and text version, additional features which are the Tarannum practice and video of Tarannum, and multimedia elements which are text, audio, video, graphic and animation. The meaning-based concept was included in this model to be applied into the Tarannum recitation as users may understand the meaning of the verses. At the same time, users can feel and internalise (tadabbur) with the Qur’an recitation.